Northeast Kansas City: a walkable district - Pendland, Konner (Kansas State University, 2020)
New Urbanism is a planning and design approach that opposes the idea of urban sprawl, a migration pattern that is very prominent in large cities, such as Kansas City. Its purpose is to combine many aspects of daily life into a singular network that enhances accessibility and quality of life. New Urbanism consists of many components that create a successful community. This study focuses on walkability and safety, two aspects of New Urbanism, that can be implemented and analyzed in any community at any scale. These principles were analyzed within the neighborhoods of Lykins and Sheffield, located east of Downtown Kansas City. These neighborhoods currently suffer from high crime rates, heavy industrial uses, and urban blight. They also lack easy access for pedestrians as well as safe and secure neighborhood environments for their residents and visitors to the area. These factors lead to the question: How can safety and walkability be analyzed and implemented in two neighborhoods within Northeast Kansas City, Lykins and Sheffield, to influence New Urbanist development in the area? This report aims to answer the preceding question by assessing the physical and perceived aspects of walkability and safety. This was achieved by using Google imagery, GIS analyses, and photo questionnaires distributed throughout the two neighborhoods. Sidewalk width, the existence of sidewalks, distances to community amenities, pavement conditions, visibility, lighting, the existence of vacant lots, and topography are the variables that have been examined throughout the study. These factors were first analyzed using GIS and Google Imagery and then were combined with the results from the photo questionnaire (n=43) to see what elements people prefer in their neighborhoods. The results from the survey and the site analysis influenced the selection of areas to implement New Urbanism design interventions. Three sites were selected that scored low in the photo survey and are considered dead zones. The design works to link these three sites together by applying similar design approaches the each location. Additional considerations were also given to walkability and safety based on survey responses to create unique experiences. These design interventions can promote New Urbanist principles and inform future development within Lykins and Sheffield as well as their surrounding neighborhoods near Downtown Kansas City.
Keywords: New Urbanism; Neighborhood; Safety; Walkability; Kansas City; Urban